1984
DOI: 10.1002/eji.1830140312
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of follicular dendritic cells from human tonsils and adenoids. II. Immunocytochemical characterization

Abstract: Follicular dendritic cells (FDC) are specialized cells found only within lymphoid follicles. They bind immune complexes and play a role in the presentation of antigen to follicular B cells and in the generation of B cell memory. In the present report the isolation of FDC from human tonsils and adenoids is described. These isolated cells have an unusual spherical arrangement and enclose lymphocytes within extensions of their membranes. Their ultrastructural features are similar to those observed in situ. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Multiple studies have examined the ultrastructure of FDCs at the tissue level Hanna and Szakal 1968;Nossal et al 1968;Kinet-Denoel et al 1982;Chen et al 1978;Mandel et al 1981;Ennas et al 1989;Tenner-Racz et al 1989;Szakal et al 1988;Imai et al 1989) and after isolation Schmitz et al 1993;Heinen et al 1984). Freshly isolated murine FDCs appear rounded and are difficult to distinguish from large lymphocytes or macrophages under the light microscope.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Multiple studies have examined the ultrastructure of FDCs at the tissue level Hanna and Szakal 1968;Nossal et al 1968;Kinet-Denoel et al 1982;Chen et al 1978;Mandel et al 1981;Ennas et al 1989;Tenner-Racz et al 1989;Szakal et al 1988;Imai et al 1989) and after isolation Schmitz et al 1993;Heinen et al 1984). Freshly isolated murine FDCs appear rounded and are difficult to distinguish from large lymphocytes or macrophages under the light microscope.…”
Section: Introductionmentioning
confidence: 96%
“…Features discernable at the electron-microscopic level include deeply indented or bilobed nuclei containing mostly euchromatin and large nucleoli. The cell body contains numerous mitochondria and vesicles, and in several places, the cytoplasm is drawn out into fine dendritic processes Schmitz et al 1993;Heinen et al 1984). FDCs trap and display antigens in the form of ICs on their membrane surfaces, which are available to interact with adjacent B lymphocytes (Heinen et al 1983;Szakal et al 1983;Tew et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…1 Macrophages, follicular dendritic cells, and fibroblasts synthesize prostaglandin E series (PGEs) as major products of arachidonic acid metabolism. [2][3][4] PGEs can be induced by a plethora of membrane-perturbing stimuli, including interleukin 1 (IL-1), tumor necrosis factor ␣ (TNF-␣), the cross-linking of Fc receptor, lipopolysaccharide (LPS), and components of the complement cascade. 1,5 Effects of PGEs result from their binding to PGE receptor subtypes, EP 2 and EP 4 , that then stimulate production of the second messenger cyclic-3Ј,5Ј adenosine monophosphate (cAMP).…”
mentioning
confidence: 99%
“…To solve this problem, we developed an experimental model by adopting FDC-like primary culture cells, HK cells, prepared from human tonsils (10). With regard to PG production in FDCs, Heinen et al (11) demonstrated for the first time that the FDCenriched cell population produces PGE 2 . Butch et al (12) also reported that inhibition of T cell proliferation by FDCs is reversed by indomethacin, suggesting that PGs are involved in FDCmediated inhibition of T cell proliferation.…”
mentioning
confidence: 99%